Prevention of Failure to Rescue in Obstetric Patients: A Realist Review. Issue 6 (4th September 2021) - Bernstein, Samantha L.; Kelechi, Teresa J.; Catchpole, Kenneth; Nemeth, Lynne S.
Abstract: Background: At least 40% of maternal deaths are attributable to failure to rescue (FTR) events. Nurses are positioned to prevent FTR events, but there is minimal understanding of systems‐level factors affecting obstetric nurses when patients require rescue. Aims: To identify the nurse‐specific contexts, mechanisms, and outcomes underlying obstetric FTR and the interventions designed to prevent these events. Methods: A realist review was conducted to meet the aims. This review included literature from 1999 to 2020 to understand the systems‐level factors affecting obstetric nurses during FTR events using a human factors framework designed by the Systems Engineering Initiative for Patient Safety. Results: Existing interventions addressed the prevention of maternal death through education of clinicians, improved protocols for care and maternal transfer, and an emphasis on communication and teamwork. Linking Evidence to Action: Few researchers addressed task overload or connected employee and organizational outcomes with patient outcomes, and the physical environment was minimally considered. Future research is needed to understand how systems‐level factors affect nurses during FTR events.